PENGARUH LOVE OF MONEY, MOTIVASI DAN RELIGIUSITAS TERHADAP KECURANGAN LAPORAN KEUANGAN DENGAN PERILAKU TIDAK ETIS SEBAGAI VARIABEL INTERVENING DAN IDEALISME DAN IDEALISME SEBAGAI VARIABEL MODERATING - Budiantoro, Harry (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
The aim of this research is to examine the influence of Love of Money, Motivation and Religiosity on Fraud in Financial Reports with Idealism as a Moderating Variable and Unethical Behavior as an Intervening Variable. This research is quantitative research, with primary data and questionnaire techniques for 30 respondents. This research was taken using simple random sampling and analyzed using the multiple linear regression method with SPSS software. The results of this research show that love of money, motivation and religiosity do not have a significant effect on the situation in financial reports. Simultaneously, love of money, motivation and religiosity have a significant effect on the condition of financial reports. Idealism cannot moderate the influence of love of money, motivation, and religiosity. Unethical behavior can mediate the influence of love of money and religiosity, while unethical behavior cannot mediate the influence of motivation on the state of financial statements. Managerial implications in this research managers need to be aware that the love of money can be the main driver of unethical behavior, research shows that individual motivation can influence the tendency to engage in unethical behavior, religiosity can reduce the tendency to be involved in financial events.